The INFLUENCE OF SPIRITUAL LEADERSHIP ON INDIVIDUAL PERFORMANCE: THE ROLE OF ORGANIZATIONAL CULTURE AS A MEDIATION - Zaid, Zaidi Salsabila; Adriani, Zulfina; Solikhin, Agus (Journal of Business Studies and Management Review, 2024)
This research aims to examine and analyze the influence of spiritual leadership on teacher performance mediated by organizational culture. The sample in this study was 47 teachers at the Tanjung Pasir Al Awwabien Islamic Boarding School, Jambi City. Data collection was carried out using the questionnaire method. The approach used in this research is to use a quantitative descriptive approach with the Partial Least Square (PLS) method. Data collection in this research is primary data. The results of this study indicate that spiritual leadership has a positive and significant effect on individual performance in teachers, spiritual leadership has a positive and significant effect on organizational culture, organizational culture has a positive and significant effect on individual performance in teachers, spiritual leadership has a positive and significant effect on individual performance which is mediated by organizational culture variables.